Covid-19 Vaccine Nationalism and International Human Rights Law - Adegbite, Olusola Babatunde; Adekola, Tolulope Anthony (The Easta Journal Law and Human Rights, 2025)
The rollout of COVID-19 vaccines was referred to as the “parallel pandemic of human rights” of some sort, running neck to neck with the pandemic itself. The production, distribution, and profiteering that followed the announcement of vaccines were so unequal, between the rich countries of the global north and their poor counterparts in the global south, that the exercise was satirically termed ‘vaccine nationalism’ or ‘vaccine apartheid’. Against the backdrop of the COVID-19 pandemic, this article examines the extent to which existing International Human Rights Law (IHRL) provides for a framework of equity in vaccine distribution across the globe, particularly in the context of pushing back ‘vaccine nationalism’. Given that the questions relating to access to vaccines sit at the intersection of intellectual property (IP) protection and human rights, the article examines the delicate balance between IP protection and the broader rights of users/society to vaccine access. The article then proceeds to discuss how far human rights jurisprudence can go in engendering access to vaccines for all.